Energy and Macronutrient Intake on Nutrional Status of Preschool Children - Ardianti, Rine Dhenok; Salimo, Harsono; Cilmiaty, Risya (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Improving the quality of Human Resources (HR) is an important thing to support the improving national development, one of which is by optimizing the nutritional status of children from an early age. The reason is nutritional problems in preschool children can reduce intelligence, productivity, and creativity which results in decreasing the quality of human resources. Besides, Preschool age is a golden period for a child for growing and developing, especially in language, cognitive, and emotional functions. Materials and Methods: This research was an observational study using a cross-sectional study design. The sample in this study was children aged 5-6 years in the Panti sub-district of Jember with the total number of samples was 138 children. The sampling method used the purposive sampling technique. Besides, the data analysis used the Spearman Rank, with a correlation test of α = 0.05, which was to analyze the relationship between the level of macronutrient consumption on the nutritional status of preschool children. Results and Discussion:. The results of the study showed that there was a correlation between energy (p= <0.001), protein (p= <0.001), fat (p= <0.001), carbohydrates (p= <0.001 ;) and maternal education (p=0.044) on nutritional status. Besides, the results test showed that the strength of the relationship between energy were: moderate (r=0.506), protein: moderate (r=0.495), fat: moderate (r=0.429), while carbohydrates: very strong (r=0.827) and Mother’s education: very weak (r = 0.172) with nutritional status. On the other hand, the father’s profession, mother’s profession, and total income had no relationship with nutritional status. Conclusion: There was a relationship between macronutrients (energy, protein, fat, and carbohydrates) and the nutritional status of preschool children. The indirect factor that had a relationship with nutritional status was maternal education. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 55-60